Five Best Management Practices in the Hotels Sector of Sri Lanka - Liyanage, Uditha (Journal of Comparative International Management)

(untitled) (Management Futures, 1999)
Six leading hotels were selected in the study of the hotel sector in an attempt to isolate the best management practices common to the sector. Two of the best practices are related to the customer in terms of creating value, while the other three are located within the people and processes of the hotel, which contribute towards operational efficiencies. Their attempt to provide engaging guest experiences as opposed to merely providing a host of amenities is particularly strategic in terms of the movement away from the limited sun and sand tourism to high-value niche marketing that has been prescribed.